WAYANG MBELING KREATIVITAS DALANG SEBAGAI KOMUNIKATOR SOSIAL - Sri Indratmi Yudiarti (Institut Seni Indonesia Surakarta, 2010)
Social phenomena and affairs happened in the society evidently have an influence on work of art creation. Wayang Mbeling (Wayang against an established convention) is one of real examples. As a work of art, this work of art is thought to violate â€œpakemâ€ (the rule) that has been the pattern for years. The violation is also committed when the puppeteer adapts the present social affair to the sphere of wayang life. The names of wayang figures and their characteristics are the same as those in â€œpakemâ€, taken from Mahabarata and Ramayana epics. The intelligent puppeteer uses his creative imagination and makes use of his inspiration in writing it. The violation of â€œpakemâ€ is interesting enough to study as the object of this research. The texts of wayang mbeling storiesÂ are studied using communication sociology approach in the form of mass communication endorsed with theories of sociology, Philosophy of art, and Cultural History. The result of this study shows that wayang mbeling can be utilized asÂ media for introducing wayang and finding an outlet for social criticism. On the other hand, wayang mbeling can be made use by the puppeteer as a means of actualizing himself as an artist. The puppetter can show that he is not only good at speaking but at writing as well. The puppeteer still has a chance of giving an entertainment to the reader because he writes the story in an informal style. The puppeteer can act as a social communicator because through his work of art he is able to convey his mission, express cultural values, and make constructive social criticism.Â Key words : puppet, wayang mbeling, creativity, social communicator.